Significant Reductions in the Area in Corroded Steel and its Repercussion in Prefabricated Large-Panel Buildings (2022)
In Santiago of Cuba, there is an architectural heritage built with the prefabricated I-464 system, popularly known as the Great Soviet Panel, with more than 50 years of use. The buildings present damages such as the corrosion of the steel in the slabs, panels and horizontal joints between them. To analyze the earthquake-resistant behavior of deteriorated buildings, it is necessary to specify the peculiarities of the steel used as reinforcement of the structural elements. Destructive testing of steel is implemented, as well as correlation of non-destructive test results with concrete, in particular ultrasonic pulse velocity, moisture, and corrosion potential. Visual inspections are also performed to identify cracking patterns, carbonation advance, and surface color. Among the main results obtained is that the quality of the steel for the 3 mm diameter bars, which make up the electro welded meshes of the panels, do not comply with the current requirements for earthquake resistant design. These bars, in addition to a yield strength higher than recommended, are smooth bars with a non-ductile behavior, since they do not have a defined elastic limit. A considerable reduction in the diameters of the corroded bars in relation to the high levels of corrosion was obtained due to the high percentages of humidity undoubtedly causing an appreciable reduction of the yield strength of these bars. It is observed that, in the elements with the highest percentages of humidity, the most negative potential values and those with the highest corrosion velocity are reached.